Mediation of industrial disputes in Liberia : enhancement precedents from the United Kingdom, New Zealand and Malaysia - Sumaworo, Mory D. A. (Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, 2019)
The industrial peace or harmony plays a pivotal role for the nations' socioeconomic growth and stability. There are lots of theories and practices through which industrial disputes can be managed and resolved. However, mediation has been proven over the years to be the most effective, efficient and expedient machinery of those practices. Therefore, this thesis explores and examines the practice of mediation of industrial disputes under Liberia's substantive and procedural laws with the aim at identifying the prospects and challenges of this important element of Alternative Disputes Resolution (ADR) in resolving industrial disputes under Liberia's labour jurisprudence. In doing so, the research was designed and carried out with a purpose to extract lessons, precedents and best practices from the following highly regulated, effective, efficient and expedient mediation jurisdictions; the United Kingdom, Malaysia and New Zealand. These prototypes were chosen due to the discovery of literature and previous research works that they have respectively better institutionalised their mediation systems of labour and industrial disputes and all of them share the Common Law legal tradition with the Republic of Liberia. Hence, the research raises and disposes no legal complication and complexity to derive lessons or the best mediation practices from these jurisdictions for Liberia. Thus, the study will help Liberia to upgrade its industrial disputes mediation structures and policies for the sustainable economic growth, social stability with shared industrial relations interests and prosperity for the employees, industries and the government. To achieve the objectives of this research and answer its questions, mixed-mood method was applied; qualitative and social legal research methods (doctrinal and non-doctrinal). The qualitative was used in all aspects of the project while quantitative or social legal research was only adopted to determine some relevant aspects of industrial disputes mediation in the Liberian labour market. As a result, the study ran an empirical survey to determine how appreciating and acceptive mediation is and what are the substantial and procedural challenges it is confronted with in Liberia? The survey therefore reveals that nearly 50% of respondents believe that mediation is the preferred method to resolve their industrial disputes. Furthermore, 82.2% and 15.5% respondents strongly agree and agree respectively that labour peace and amicable resolution can boost the Sustainable Economic Growth (SEG). On the other hand, the survey also reveals that 72.9% of the respondents strongly agreed that industrial peace and harmony can lead to Social Stability (SS). The research eventually recommends, among other things the enactment of a specialized mediation or ADR Act by the national legislature to effectively formalize and institutionalize the practice. Likewise, the study calls for the establishment of a Institute of Labour Studies (ILS) and an Independent Mediation Centre (IMC) in Liberia to provide training and capacity building programmes, conduct studies and identify challenges in the nation's labour market. Besides, the thesis further calls for instituting an effective Labour Inspectorate System (LIS) making sure that industrial and employment laws and policies are adhered to by all the stakeholders. It also proposes a 'Practice Direction on Mediation of Civil Cases to the Judiciary' (the Supreme and subordinate courts) as a way forward to encouraging the court-annexed mediation and amicable resolution to some mediatable civil cases. These, along with other recommendations, will serve as prompts to the followings: i) Enhancement of industrial peace and harmony. ii); Reduction on labour disputes resulted from non-compliance with laws and policies and iii) Sustainable development, economic growth and shared interests for the workers and industries via healthy industrial and workplace relationship.